An observational objective job analysis of role related tasks undertaken by Royal Navy sailors. - Hogan, Joseph A.; Powell, Steven D.; Gribble, Hannah; Saunders, Samantha; Gunner, Frances; Fallowfield, Joanne L.; Brown, Piete E.H.; Allsopp, Adrian J. (Work, 2024)
BACKGROUND: The current in-service Royal Naval Fitness Test has two elements to test the aerobic endurance and muscular strength of Service Personnel through generic field-based tests and a short job task simulation. However, in 2017 the Royal Navy (RN) identified a requirement to update their in-service fitness test to align with international best practice. OBJECTIVE: The purpose of this study was to conduct an Objective Job Task Analysis on critical, physically demanding tasks that could be undertaken by RN sailors during sea deployments METHODS: Twenty-one training exercises were observed across a range of contexts; Type 23 Frigates, Type 45 Destroyers and at shore-based training facilities. A total of 203 RN personnel (age 27.8±7.1 years) were observed undertaking 36 job related tasks (e.g., 'firefighting', 'damage control', 'abandon ship' and 'casualty handling'). Tasks were evaluated by cardiovascular response, primary functional movements and contextual factors to aid a Military Judgement Panel in task list down-selection. RESULTS: 14 Criterion Tasks (e.g., 'firefighting', 'two-person magazine stowage' and 'casualty handling') were selected to progress to the next stage of the process. Five tasks were selected based on cardiovascular responses and a further nine tasks selected based on task ergonomics and other factors. CONCLUSION: This research has identified and quantified the most physically demanding, critical roles undertaken by RN sailors on sea deployments and will inform the development of the RN Physical Employment Standard.